1990
DOI: 10.1099/0022-1317-71-9-1999
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and purification of a non-A, non-B hepatitis-associated microtubular aggregates protein

Abstract: Blood-borne type non-A, non-B (NANB) hepatitisassociated microtubular aggregates protein was isolated and partially sequenced. The microtubular aggregates were isolated from the hepatocytes of NANBinfected chimpanzees and were found to have a buoyant density in sucrose solution of 1.21 to 1-23 g/ml. A single protein, recognized by our anti-microtubular aggregates monoclonal antibodies, was found to have an M~ of 44 000 (p44). This p44 protein was not found in uninfected chimpanzees. We determined a partial ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 24 publications
(24 reference statements)
0
24
0
Order By: Relevance
“…Increased expression within the original tester material was checked by quantitative competitive RT-PCR, a technique which had been established using primer pairs designed on the basis of the database entries (Table 1). Relative to the reference tran-scripts glyceraldehyde-3-phosphate dehydrogenase (G3PDH, ␤-actin, and albumin, and compared to the original driver RNA preparation, transcripts of four genes were found to be elevated severalfold in the tester material (Table 2): (i) the chemokine IP-10 gene, originally described as an IFN-␥-inducible early-response gene (26,48); (ii) the IFN-␣-regulated antiviral MxA gene (1,40); (iii) the gene encoding the IFN-␣/␤-inducible 44-kDa microtubular polypeptide (p44) formerly shown to be associated with cytoplasmic ultrastructural entities in hepatocytes of chimpanzees inoculated with sera from patients suffering from non-A, non-B hepatitis (21,24,27,46); and (iv) the gene encoding the IFN-␣/␤/␥-inducible 56-kDa protein (IFI-56K) recently described to interact with the eukaryotic translation initiation factor eIF-3 (7, 50). The differential screening hybridization showed that all clones represents low-abundance transcripts in the HCV-infected liver, since they were detectable with the labeled subtracted probe but not with the labeled tester probe (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased expression within the original tester material was checked by quantitative competitive RT-PCR, a technique which had been established using primer pairs designed on the basis of the database entries (Table 1). Relative to the reference tran-scripts glyceraldehyde-3-phosphate dehydrogenase (G3PDH, ␤-actin, and albumin, and compared to the original driver RNA preparation, transcripts of four genes were found to be elevated severalfold in the tester material (Table 2): (i) the chemokine IP-10 gene, originally described as an IFN-␥-inducible early-response gene (26,48); (ii) the IFN-␣-regulated antiviral MxA gene (1,40); (iii) the gene encoding the IFN-␣/␤-inducible 44-kDa microtubular polypeptide (p44) formerly shown to be associated with cytoplasmic ultrastructural entities in hepatocytes of chimpanzees inoculated with sera from patients suffering from non-A, non-B hepatitis (21,24,27,46); and (iv) the gene encoding the IFN-␣/␤/␥-inducible 56-kDa protein (IFI-56K) recently described to interact with the eukaryotic translation initiation factor eIF-3 (7, 50). The differential screening hybridization showed that all clones represents low-abundance transcripts in the HCV-infected liver, since they were detectable with the labeled subtracted probe but not with the labeled tester probe (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The application of SSH to liver tissue from patients with chronic HCV infection as tester and non-HCV-infected patients as driver, the subsequent screening procedure, and the confirmatory controls revealed four genes which are expressed within the HCV-infected tissue to a higher degree than the noninfected control: (i) the CXC or alpha chemokine IP-10 gene (26,48), (ii) the antiviral MxA gene (1,40), (iii) a gene encoding a 44-kDa protein reported to be associated with ultrastructural changes in hepatocytes of chimpanzees infected with non-A, non-B hepatitis sera (21,24,27,46), and (iv) a gene encoding 56-kDa interferon-inducible protein which was recently shown to interact with eIF-3 (7,50). All of these genes are inducible by IFN-␥ (IP-10), IFN-␣/␤ (MxA and p44), or both (IFI-56K).…”
Section: Discussionmentioning
confidence: 99%
“…LMP1 up-regulates expression of vimentin intermediate filaments, a p55 actin bundling protein, MARCKS, LFA-1, LFA-3, and ICAM-1 (10,13,47,101,106,107,(114)(115)(116). GS3686, the most highly EBV-induced mRNA, encodes a putative microtubule aggregating protein (43,103). PSCDBP binds to cytoadhesin 1 (61), and BASP1 is an N-terminally myristolated, Ca ϩ and calmodulin binding protein found in plasma membrane microdomains.…”
Section: Vol 76 2002 Ebv Effects On Cell Mrnas 10431mentioning
confidence: 99%
“…Shimizu et al (182) developed from human lymphocytes a monoclonal antibody that immunoreacted with liver biopsy material obtained from both HDV-and HCV-infected animals (183). The monoclonal antibody detects the presence of microtubule aggregates that apparently are synthesized in response to HDV or HCV infection (98,197).…”
Section: Modelsmentioning
confidence: 99%